Localização de estados quânticos em cadeias de spins com anisotropia - Sousa, Márcio Guimarães de (2024)
The principles of ergodicity and thermalization constitute the foundation of sta- tistical mechanics, stablishing that a many-body system loses progressively its local in- formation as it evolves in time. Nevertheless, these principles can be disrupted when thermalization dynamics lead to the conservation of local information, as observed in the phenomenon known as many-body localization. Quantum spin chains provide a fun- damental platform for exploring the dynamics of closed interacting quantum many-body systems. This study explores the dynamics of a spin chain with ≥ 1/2 within the 1 −2 (or Majumdar-Ghosh) model, incorporating a non-uniform magnetic field and single-ion anisotropy. Employing exact numerical diagonalization, we unveil that a nearly constant- gradient magnetic field suppress thermalization, a phenomenon termed Stark many-body localization (SMBL), previously observed in = 1/2 chains. Furthermore, our findings re- veal that the presence of single-ion anisotropy alone is sufficient to prevent thermalization in the system. Interestingly, when the magnitudes of the magnetic field and anisotropy are comparable, they compete, favoring delocalization. Despite the potential hindrance of SMBL by single-ion anisotropy in this scenario, it introduces an alternative mechanism for localization. Our interpretation, considering local energetic constraints and resonances between degenerate eigenstates, not only provides insights into SMBL but also opens ave- nues for future experimental investigations into the enriched phenomenology of disordered free localized ≥ 1/2 systems.